(3JGQjN CSeGA GdKbGJ eef fbd Yfge GdYde Ydi MQha GdeYLes - (3CHh MaU YeQ Hf TGgjf GdHZOGOj GdhGYX,J (B385 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje Yhfc Gddge CNHQfG GdTjN CHh YHO Gddg eMeO Hf CHj fUQ Hf YHO Gddg GdMejOi Yf CHj MaU YeQ Hf CMeO Hf TGgjf GdhGYX QMeg Gddg bGd cJGH CSeGA GdKbGJ eef Qhi GdMOjK eef GfJgi EdjfG PcQg s
(3BNQgG (B:s
(3bGd Ydi Hf Sgd bGd SeYJ CMeO Hf MfHd ai OYdjR YaGf jbhd dYHO Gddg Hf GdQhei jbhd djJ CHG RcQjG bO bOe jYfi GHf eYjf bGd cGf jbGd NPhG GdMOjK ef GdKbGJ BNQ cJGH JGQjN CSeGA GdKbGJ s
(3GdfSNI HgG MhGTs
(3HBNQ GdfSNI KdGK hQbGJ efaQOI dYdgG ef GdfSNIs
(3HChdg hbajIs
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B40s
Keywords: (3GdJGQjNs